2022
DOI: 10.1007/s11739-022-03060-3
|View full text |Cite
|
Sign up to set email alerts
|

Handgrip strength is associated with adverse outcomes in patients hospitalized for COVID-19-associated pneumonia

Abstract: Handgrip strength (HGS), a simple tool for the evaluation of muscular strength, is independently associated with negative prognosis in many diseases. It is unknown whether HGS is prognostically relevant in COVID-19. We evaluated the ability of HGS to predict clinical outcomes in people with COVID-19-related pneumonia. 118 patients (66% men, 63 ± 12 years), consecutively hospitalized to the “Santa Maria” Terni University Hospital for COVID-19-related pneumonia and respiratory failure, underwent HGS measurement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 25 publications
(29 reference statements)
0
9
0
1
Order By: Relevance
“…Handgrip strength is a valid indicator of general health and a powerful predictor of disability, morbidity, and mortality across all life stages [ 51 , 52 , 53 , 54 ]. During an acute COVID-19 episode, low handgrip strength has been associated with an increased risk of hospitalization and poor outcomes [ 55 , 56 , 57 ]. In adults who survived severe COVID-19, handgrip strength values after six months of hospital discharge were significantly lower than the healthy controls [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Handgrip strength is a valid indicator of general health and a powerful predictor of disability, morbidity, and mortality across all life stages [ 51 , 52 , 53 , 54 ]. During an acute COVID-19 episode, low handgrip strength has been associated with an increased risk of hospitalization and poor outcomes [ 55 , 56 , 57 ]. In adults who survived severe COVID-19, handgrip strength values after six months of hospital discharge were significantly lower than the healthy controls [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mesmo que alguns estudos (TUZUN et al, 2021;;PUCCI et al, 2022;CHEVAL et al, 2021) vêm reportando o crescimento do uso do dinamômetro manual em ambiente hospitalar, para melhor quantificação da força muscular periférica, o MRC é considerado um método válido, confiável e de fácil aplicação (TURAN; TOPALOGLU; OZYEMISCI., 2020). Independente da ferramenta a ser utilizada, avaliar a força muscular de pacientes infectados pós COVID-19 é de fundamental importância para o acompanhamento clínico e intervenção precoce, uma vez que a fraqueza muscular periférica impacta negativamente nas atividades do dia a dia e pode trazer restrições a longo prazo (KARA et al, 2021).…”
Section: Discussionunclassified
“…As in most severe infections, muscle mass seems to be negatively affected in COVID-19 patients [ 25 ]. At the same time evidence suggests that limited muscle function can be associated with a higher risk of severe COVID-19 disease [ 26 ]. Moreover, results from a recent study indicated that handgrip strength (HGS) can be used as a risk predictor of future short-term adverse clinical events, such as endotracheal intubation for COVID-19 patients [ 27 ].…”
Section: Introductionmentioning
confidence: 99%